Adsorption of Silicate Anions from Geothermal Brine Using Chitosan-Polyethylene Glycol Composite to Prevent Silica Scaling on the Dieng Geo Dipa Geothermal Energy System - Nur Hayati; Hanik Humaida; Dwi Siswanta (Indonesian Journal of Chemistry, 2021)
Silica scaling is a common problem in geothermal power generation facilities which inhibits electricity generation. In order to provide a solution to this problem, the removal of silicate ions using CPEG-TOMAC (Chitosan-polyethylene glycol–trioctyl methyl ammonium chloride) membrane adsorbent was investigated for geothermal brine from Geo Dipa Energy, Dieng. The process is dependent on contact time, pH, and the concentration of silicate. An adsorption batch study that used adsorbents for the geothermal brine of the Dieng Geo Dipa reactor 28A showed that CPEG TOMAC at pH 6 resulted in an adsorption capacity of 72.6 mg g–1. Furthermore, the adsorption of silicate ions onto the membrane followed pseudo-second-order kinetics and the Freundlich isotherm model.